ΔCT Value of Amplified Refractory Mutation System Predicts Efficacy of EGFR-TKIs in Advanced Non–Small-Cell Lung Cancer: A Multi-Center Retrospective Study - Chen, Min; Huang, Wenqi; Yang, Dongyong; Huang, Jincheng; Li, Gong; Wang, Xiaoqing; Xiao, Nanjie; Zhang, Weijian; Guan, Jian; Wang, Shuang; Liu, Laiyu (Frontiers in Molecular Biosciences, 2021)
Purpose: This multi-center retrospective study determines whether the ΔCT value of the Amplified Refractory Mutation System (ARMS) predicts the efficacy of epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) in EGFR-mutant advanced non–small-cell lung cancer (NSCLC). Patients and methods: Patients who harbored an exon 19 deletion (19Del) or L858R mutation detected by the ARMS and previously received treatment of EGFR-TKIs as a monotherapy were enrolled. A total of 108 NSCLC patients in four hospitals were enrolled. We divided the patients into a high ΔCT group (Group H) and a low ΔCT group (Group L) by the Martingale residuals analysis and log-rank test. The primary outcome was progression-free survival (PFS). Univariate analysis and multivariable regression were applied to compare the PFS between the groups. Result: The Martingale residuals analysis and log-rank test were applied to find the cutoff ΔCT value (0.8). In the 108 patients we enrolled, 59 were in group L and 49 were in group H. Patients’ demographics and clinical characteristics, including age, sex, smoking history, pathology, mutation sites, TNM stage, and line of TKIs therapy, were not significantly different between group L and group H. The median PFS was 11.1 months in group L and 6.9 months in group H, and the difference showed statistical significance (p < 0.001). Moreover, the objective response rates (ORRs) in group L was significantly higher than in group H (61.0 vs 34.7%, p = 0.002). The median OS was 25.0 months in group L and 20.0 months in group H (p = 0.046). Conclusion: The ΔCT value of ARMS could be an efficacy predictor for EGFR-TKI treatment in advanced EGFR-mutant NSCLC.